Overview of Complementarity and Synergy with Other Wavelengths in Cosmology in the SKA era - Takahashi, K.; Brown, M.; Burigana, C.; Jackson, Carole; Jarvis, M.; Kitching, T.; Kneib, J.; Oguri, M.; Prunet, S.; Shan, H.; Starck, J.; Yamauchi, D. (Proceedings of Science, 2015)
We give an overview of complementarity and synergy in cosmology between the Square Kilometre Array and future survey projects in other wavelengths. In the SKA era, precision cosmology will be limited by systematic errors and cosmic variance, rather than statistical errors. However, combining and/or cross-correlating multi-wavelength data, from the SKA to the cosmic microwave background, optical/infrared and X-ray, substantially reduce these limiting factors. In this chapter, we summarize future survey projects and show highlights of complementarity and synergy, which can be very powerful to probe major cosmological problems such as dark energy, modified gravity and primordial non-Gaussianity.